Politics in the Family: Nepotism and the Hiring Decisions of Italian Firms - Stefano Gagliarducci; Marco Manacorda (Institute for the Study of Labor (IZA), 2016)
In this paper we investigate the effect of family connections to politicians on individuals' labor market outcomes. We combine data for Italy over almost three decades from longitudinal social security records on a random sample of around 1 million private sector employees with the universe of around 500,000 individuals ever holding political office, and we exploit information available in both datasets on a substring of each individual's last name and municipality of birth in order to identify family ties. Using a diff-in-diff analysis that follows individuals as their family members enter and leave office, and correcting for the measurement error induced by our fuzzy matching method, we estimate that the monetary return to having a politician in the family is around 3.5 percent worth of private sector earnings and that each politician is able to extract rents for his family worth between one fourth and one full private sector job per year. The effect of nepotism is long lasting, extending well beyond the period in office. Consistent with the view that this is a technology of rent appropriation on the part of politicians, the effect increases with politicians' clout and with the resources available in the administration where they serve.
Keywords: D72; D73; H72; J24; J30; M51; 330; Nepotism; family connections; politics; rent appropriation